Transcription of the Rod-Shaped Viruses SIRV1 and SIRV2 of the Hyperthermophilic Archaeon Sulfolobus - Kessler, Alexandra (American Society for Microbiology, 2004)
The double-stranded DNA genomes of the crenarchaeal rudiviruses SIRV1 (32 kb) and SIRV2 (35 kb) were previously sequenced. Here we present results of the analysis of gene expression of these viruses at different time points after infection of the host cell, Sulfolobus islandicus, and of the mapping of transcriptional start sites. Transcription of both genomes starts simultaneously at multiple sites spread over the total length of the genome and from both strands. The earliest time point when viral transcripts could be detected in cells was 30 min after infection. At this time point all the viral genes, except one, were transcribed. Many genes were clustered and appeared to be transcribed as polycistronic messengers. Although the coat protein-encoding gene was initially also transcribed as a polycistronic messenger, an abundant monocistronic transcript of this gene was detected 2 to 3 h after infection, just before assembly of viral particles. The expression of a single gene, adjacent to the coat protein gene, was upregulated at the late phase of infection, suggesting that it might be involved in specific processing and activation of the coat protein messenger. Start sites of 13 transcripts from the SIRV1 genome have been mapped by primer extension, and promoter sequences have been identified. Similar to host promoters, these viral promoters all contain potential binding sites for the archaeal transcription factors TATA binding protein and transcription factor B. In addition, most of them contain a virus-specific consensus element, suggesting the involvement of alternative transcription factors.